Political Parties' Campaign Financing in Ghana's Fourth Republic: A Contribution to the Discourse. (December 2017) - Arthur, Peter
The period from 1992 saw Ghana, under pressure from both internal and external sources, embark on the transition to democratic rule. Despite the strides, an issue that has the potential to undermine Ghana's liberal democratic credentials has centred on the process of political party financing. The purpose of this paper is to analyse how the existing political party financing system in Ghana is negatively impacting on electoral competition and the country's democratic process. Drawing on secondary sources, this paper shows that, given that it is political resources that drive party vibrancy and competitiveness, a level playing field in terms of public financing of political parties can help in electoral competition and the promotion of the democratic process in Ghana. However, the importance of transparency and accountability, as well as a legal framework that monitors, denounces, sanctions and punishes abuse in the use of public funds, would be crucial if success is to be attained.